Intranet Design Strategies - Rohith Roshan Devu; Subba Rao Katta (Institute of Advanced Engineering and Science, 2016)
The intranets have been deployed extensively in large and small-scale organizations. It has grown rapidly by offering features like collaborative communication channels, easing the business processes etc. Typically organizations faced difficulties but they are prevalent while implementation. But the organizations lack clear strategies in designing intranet. It leads to loss on investment, time and productivity, a complete intranet failure. Previous studies mainly focused on management, security and usage etc. This paper presents 9 design strategies for intranet addressing system oriented plan that can be applied in real-time to achieve improvement in organizational performance.